دراسة مقارنة بين تأثير الزعانف العمودية والمائلة على أداء المقطر الشمسي - بن علي, لويزة; مومن مسعود, سارة (university of eloued جامعة الوادي, 2023)
تفاقم مشكلة نقص المياه الصالحة للشدرب فدي المنداطق المعزولدة دفعندا لاسدتغلال تقنيدة التقطيدر الشمسدي لتحليدة الميداه المالحدة. تدم تحسدين أداء المقطدر الشمسدي البسديط عدن طريدق إضدافة زعدانف حديدية حيا زادت مساحة التقداط الإشدعاع الشمسدي وفتدرة تخدزين الطاقدة ولكدن ظدل الزعدانف أثدر على إنتاجية المقطر. قمنا في هذا العمل التجريبي بمقارنة أداء ثلاث مقطرات شمسية بسديطة تحتدوي كل منها على صفيحة حديدية بنفز الأبعاد يحتوي أحدهما على زعانف حديدية عمودية وااخر علدى 1.2 وإرتفاعهدا cm زعانف حديدية مائلة بزاوية ° 45 عن الأفق لهذه الزعانف نفز الأبعداد )قطرهدا 3( و الثالا شاهد أظهرت النتائج أن استخدام الزعانف الحديدية خاصة الزعانف المائلة يعزز cm أداء المقطرات الشمسية حيا تم تحسين إنتاجية المقطر المحسن بالزعدانف المائلدة بنسدبة % 70.32 و تحسين إنتاجية المقطر المحسن بالزعانف العمودية بنسبة % 37.75 مقارنتا بالمقطر الشاهد.The exacerbation of the problem of lack of potable water in isolated areas prompted us to exploit the solar distillation technique to desalinate salty water. The performance of the single slope solar distiller was improved by adding iron fins, as the solar radiation capture area and energy storage period were increased, but the shadow of the fins affected the distiller's productivity. In this experimental work, we compared the performance of three single slope solar distillers, each containing an iron plate with the same dimensions, first distiller containing vertical iron fins and the second distiller containing iron fins inclined at an angle of 45° from the horizon, these fins have the same dimensions (1.2 cm in diameter and 3 cm in height), and the third distiller is a witness. The results showed that the use of iron fins, especially the oblique fins, enhances the performance of solar distillers, as the productivity of the improved distiller with oblique fins was improved by 70.32%, and the productivity of the improved distiller with vertical fins was improved by 37.75% compared to the witness distiller.
مذكرة ماستر فيزياء
Keywords: مقطدر شمسدي بسديط زعدانف عموديدة زعدانف مائلدة تخدزين الطاقدة الإشدعاع الشمسي ماء مقطر.; Single slope solar distiller, Vertical fins, Blique fins, Energy storage, Solar radiation, Distilled water.